The Local and Electronic Structure Study of LuxGd1−xVO4 (0 ≤ x ≤ 1) Solid Solution Nanocrystals - Yang Chen; Ziqing Li; Nianjing Ji; Chenxi Wei; Xiulan Duan; Huaidong Jiang (Nanomaterials, 2023)
Rare-earth-doped mixed crystals have demonstrated tunable optical properties, and it is of great importance to study the structural characteristics of the mixed-crystal hosts. Herein, LuxGd1-xVO4 (0 ≤ x ≤ 1) solid solution nanocrystals were synthesized by a modified sol–gel method, with a pure crystalline phase and element composition. The X-ray diffraction (XRD) and Rietveld refinement results showed that LuxGd1−xVO4 nanocrystals are continuous solid solutions with a tetragonal zircon phase (space group I41/amd) and the lattice parameters strictly follow Vegard’s law. The detailed local structures were studied by extended X-ray absorption fine structure (EXAFS) spectra, which revealed that the average bond length of Gd-O fluctuates and decreases, while the average bond length of Lu-O gradually decreases with the increase in Lu content. Furthermore, the binding energy differences of core levels indicate that the covalent V-O bond is relatively stable, while the ionicity of the Lu-O bond decreases with the increasing x value, and the ionicity of the Gd-O bond fluctuates with small amplitude. The valence band structures were further confirmed by the first-principles calculations, indicating that the valence band is contributed to by the O 2p nonbonding state, localized Gd 4f and Lu 4f states, and the hybridized states between the bonding O 2p and V 3d. The binding energies of the Lu core and the valence levels tend to decrease gradually with the increase in Lu content. This work provides insight into the structural features of mixed-crystal hosts, which have been developed in recent years to improve laser performance by providing different positions for active ions to obtain inhomogeneous broadening spectra.